2022
DOI: 10.1002/adom.202201500
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex SERS Phenotyping of Single Cancer Cells in Microdroplets

Abstract: In the context of personalized medicine, the analysis of single cells is key in order to understand the origin and evolution of cancer to provide an accurate prognosis. Microfluidics and microdroplets are increasingly used for the handling and understanding of the behavior of single cells, as they offer the perfect isolated environment. However, due to the small volumes handled, it is necessary to couple this technology with an ultrasensitive detection technique. Herein, surface‐enhanced Raman scattering (SERS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Oliveria et al developed a SERS-based microfluidic sensor capable of multiplex phenotype analysis of single cancer cells (Fig. 7 ) [ 53 ]. Cancer cells labeled with different SERS nanotags capable of recognizing membrane proteins were individually encapsulated in microdroplets.…”
Section: Classification Of Microfluidic Devices For Sers Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveria et al developed a SERS-based microfluidic sensor capable of multiplex phenotype analysis of single cancer cells (Fig. 7 ) [ 53 ]. Cancer cells labeled with different SERS nanotags capable of recognizing membrane proteins were individually encapsulated in microdroplets.…”
Section: Classification Of Microfluidic Devices For Sers Detectionmentioning
confidence: 99%
“…The proportions of elements in this figure are not accurately represented to scale. Reprinted with permission from [ 53 ]. Copyright 2023 Wiley-VCH Verlag GmbH & Co …”
Section: Classification Of Microfluidic Devices For Sers Detectionmentioning
confidence: 99%
“…On the distinction of different cell populations, Teixeira et al demonstrated the potential of the SERS technique to detect the profiles of different cell types (malignant and non-malignant) and to distinguish them based on spectral differences [214]. In a recent study, Oliveira et al demonstrated the multiplex phenotyping of single cancer cells using SERS probes [215]. Furthermore, the possibility to detect DNA mutations using SERS was also demonstrated.…”
Section: Surface-enhanced Raman Scattering For Diagnosis Of Amlmentioning
confidence: 99%
“…In a TOC study conducted by Yang et al 105-106 protein copies were detected per cell using MALDI MS (with a spatial resolution of 50 um) combined with a microfluidic approach for sample preparation, a combination coined "MIMAS" (Microfluidic assay combined with MALDI Mass Spectrometry). This study and another past work allowed Yang et al to develop a method that does not require fluorescent-based method for detecting highly abundant proteins from a cell [74][75][76]. In this study isotope-labeled peptides were used as internal standards to quantify the presence of protein Bcl-2, known to be a key regulator in cell apoptosis [74].…”
Section: Mass Spectrometrymentioning
confidence: 99%